Continuous Inhibition of Sonic Hedgehog Signaling Leads to Differentiation of Human-Induced Pluripotent Stem Cells into Functional Insulin-Producing β Cells - Song Lee; Jae Hyun Joo; Ju Yun Oh; Eun Ha Seo; Yang Hee Kim; Eunsung Jun; In Kyong Shim; Song Cheol Kim (Stem Cells International, 2021)
Human-induced pluripotent stem cell- (iPSC-) derived insulin-producing cells (IPCs) can be used for islet cell transplantation into type 1 diabetic patients and as patient-specific cells for the development of novel antidiabetic drugs. However, a method is needed to generate functional IPCs from iPSCs and simplify the protocol. We compared combinations of small molecules that could induce the differentiation of cells into a definitive endoderm and preferentially into islet precursor cells. When generated using an optimal combination of small molecules, IPCs secreted insulin in response to glucose stimulation. We constructed spheroid IPCs and optimized the culture and maturation conditions. Quantitative PCR revealed that the expression of definitive endoderm-specific markers differed depending on the combination of the small molecules. The small molecule, N-[(3,5-dimethyl-1-phenyl-1H-pyrazol-4-yl)methylene]-4-(phenylmethyl)-1-piperazinamine, induced the differentiation of cells into functional IPCs by inhibiting Sonic hedgehog signaling. Images of the 2D culture showed that IPCs formed spheroids from day 5 and continuously secreted insulin. We developed a simple differentiation method using small molecules that produced functional IPCs that responded to glucose stimulation within a relatively short period. We posit that this method along with further refinement of the differentiation process can be applied to culture IPCs that can be used in clinical trials.